The complement pathway and the pathophysiology of fibroproliferative cutaneous scarring - Kruglikov, Ilja L.; Walendzik, Katarzyna; Scherer, Philipp E. (Frontiers in Immunology, 2025)
Fibroproliferative cutaneous pathologies such as hypertrophic scars and keloids have a high prevalence after burns and surgical interventions; however, their pathophysiology remains not fully understood. Here, we formulate a new pathophysiology of cutaneous scarring based on the primary involvement of the dysregulated complement pathway. This pathway is activated in skin wounds to promote their closure and is directed, among others, against S. aureus, bacteria that are always present at the site and time of injury. Under some conditions, this can lead to intensive proliferation of S. aureus, changing the status of these bacteria in the skin from commensal to pathogenic. Pathogenic S. aureus recruits complement factor H (CFH) – a key recognition molecule for the host-vs-target identification - to its surface to evade the immune system. This provides an effective suppression of the CFH level in the wound and increases the probability of the production of membrane attack complexes (MACs). The production of MACs can cause an enhanced autolysis of the host cells. This is counter-productive in wound closure. Defensive mechanisms are activated in these cells. One of them is the CAV1-dependent endocytosis that effectively eliminates MACs from cell membranes. This consistently leads to a reduction of the CAV1 content in affected skin areas, causing the established hallmark of hypertrophic scarring (HTS) and keloids (KE), as well as overexpression of RUNX2, which promotes the formation of the cartilage-like hyalinated scar tissue. According to this pathophysiology, future efforts in the prevention and treatment of scarring should be concentrated on the reduction of bacterial content in the wound in combination with a proper modulation of the complement pathway and CAV1 in wounded skin.